Mechanical modeling of thermal barrier coatings at high temperatures - Hermosilla, Unai (2008)
Thermal barrier coatings (TBCs) are usually applied on high temperature gas turbine components. They reduce the need for additional cooling of the exposed surfaces and improve the durability of the underlying materials. However, the lack of reliable lifting methods limits their applicability in the design of turbine components and so they are usually employed as additional protection for components that already meet the design requirements.